Data journalism in the contemporary political sphere between 2015 and 2025: scoping review - Rodríguez-Urra, Carlos; Elórtegui-Gómez, Claudio; Jimenez-Chavez, Daniel (Estudios sobre el Mensaje Periodístico, 2026)
Data journalism has emerged as a specialisation associated with strong democratic potential. Newsrooms increasingly rely on data visualisation to show social and political trends, drawing on public information from state institutions and private companies. This process has been accelerated worldwide by information and communication technologies. his article presents a scoping review of the relationship between data journalism and politics over the past decade. Using the SALSA methodology (Search, Appraisal, Synthesis and Analysis), it maps 101 academic sources to examine how data journalism contributes to political communication, transparency and democratic accountability. The analysis delineates seven research fronts: democracy; disinformation and social media; visualisation and political race; investigative and collaborative journalism; automation and objectivity; open data and literacy; and studies from the MENA region. The concept of democracy emerges as the central axis, with data journalism being positioned as both a methodological innovation and a democratic watchdog. The findings reveal geographical asymmetries, with Western scholarship prevailing while research from Asia, Africa and Latin America remains limited. The study also highlights the ethical tensions between algorithmic dependence, political influence and objectivity. Data journalism functions as a technological and political praxis, engendering transparency, civic engagement and democratic renewal.
Keywords: Disinformation; Data journalism; politics; media system; precision journalism